2012
DOI: 10.1148/radiol.11111299
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Effects of Cognitive Rehabilitation on Structural and Functional MR Imaging Measures—An Explorative Study

Abstract: Rehabilitation of attention and information processing and executive functions in RR MS may be effected through enhanced recruitment of brain networks subserving the trained functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(194 citation statements)
references
References 46 publications
12
171
5
2
Order By: Relevance
“…Interestingly enough, changes in RS FC connectivity of cognitive-related networks helped to explain the persistence of the effects of cognitive rehabilitation in the patients several months after treatment termination and the patients improvement on depression and quality of life scales, suggesting that cognitive rehabilitation exerts a positive effect that is not limited to the trained function but extends to several additional domains. 60 Notably, the previous study 59 found no structural changes in the GM and NAWM following cognitive rehabilitation. Such a negative finding might reflect an impairment of structural plasticity in these patients, which is likely to be caused by the MS pathological process.…”
Section: Msmentioning
confidence: 86%
“…Interestingly enough, changes in RS FC connectivity of cognitive-related networks helped to explain the persistence of the effects of cognitive rehabilitation in the patients several months after treatment termination and the patients improvement on depression and quality of life scales, suggesting that cognitive rehabilitation exerts a positive effect that is not limited to the trained function but extends to several additional domains. 60 Notably, the previous study 59 found no structural changes in the GM and NAWM following cognitive rehabilitation. Such a negative finding might reflect an impairment of structural plasticity in these patients, which is likely to be caused by the MS pathological process.…”
Section: Msmentioning
confidence: 86%
“…[25][26][27][28] This may be explained at least in part by several factors: lesions in "eloquent" brain areas such as the optic nerves are more likely to be clinically expressed than lesions in less eloquent pathways; the degree of matrix and axonal destruction may vary; and the potential exists for rapid symptom recovery. [29][30][31][32][33][34][35][36][37][38] Even patients with progressive forms of MS, particularly those with Gd+ lesions indicating a subclinical relapse, may respond clinically to disease-modifying therapies (DMTs). For example, in a post hoc analysis of the Olympus trial of rituximab in PPMS, patients with Gd+ lesions had a significantly better response to treatment than those without Gd+ lesions.…”
Section: Background Historical Evolution Of Ms Diagnostic Criteriamentioning
confidence: 99%
“…Historically, most of the intervention implemented for use with MS patients involved learning and memory-based interventions, 15 but recently the focus has moved to other domains such as executive function and attention 21,23,30,31,32,47,48,49 , since these are the cognitive functions that have been shown to be most affected by MS. Interventions based on these functions appear to lead to more consistent results.…”
Section: Introductionmentioning
confidence: 99%